DNA barcoding Aotearoa New Zealand’s ray-finned fishes (Actinopterygii) : a reference database and use case : this thesis is completed in partial fulfilment of a Masters of Biological Science Degree, Massey University, New Zealand. - MacLean Stones, Maddie (Massey University, 2022)
DNA barcode reference databases have been created for the fish biodiversity of many nations, providing a resource to facilitate rapid species identification, biodiversity assessment, and ultimately greater awareness and understanding of freshwater and marine fish fauna. Aotearoa New Zealand (NZ) has a wide diversity of marine, estuarine, and freshwater habitats that comprise a diverse fish fauna, and a high proportion of endemic fish species. Even so, a DNA barcode reference database for the fishes of NZ has not yet been created. In this thesis, I curated a DNA barcode reference database for NZ fishes based on the Cytochrome Oxidase I (COI) gene region using previously published sequences from open-access repositories (i.e., Nucleotide Sequence Database Collaboration, and the Barcode of Life Data System) and novel sequences generated for species not previously sequenced (Chapter 2). To demonstrate the utility of this database, I then provide a use case to genetically identify larval fishes collected off the Northeast Coast of the North Island of NZ and compare these identities to those based on morphology (Chapter 3). To ensure representativeness and integrity of the sequence data within the NZ Fish Barcode Database, I preferentially generated sequences from fish specimens that had been identified by an expert taxonomist or held in museum collections. Furthermore, for widespread species that I did not have sequences for, I sought sequences from specimens collected as geographically close to NZ as possible. In Chapter 2, I was able to generate and retrieve sequences for 965 of the 1320 fish species recorded in NZ (73%); I provide a summary of our progress toward generating a DNA barcode reference database for NZ’s fish biodiversity and report interspecies genetic divergences (based on Kimura-2-pairwise distance) between species. In Chapter 3, the database use case, I found that larvae were often able to be identified to their taxonomic family based on morphological features, but in some cases their taxonomic affinities were unknown. DNA barcoding enabled us to identify the species identity of the larval fishes with reference to the NZ Fish Barcode Database. Overall, our generated DNA barcode reference database is a practical resource of value for future environmental DNA studies, biodiversity monitoring, and managing fisheries and commercial fisheries derived products.
Keywords: 300504 Fish physiology and genetics; 310509 Genomics